Interaction of RECQL4 with poly(ADP‐ribose) is critical for the DNA double‐strand break response in human cells - Sunyoung Shin; Dongmin Kim; Hyemi Kim; Won‐Ho Cho; Gyungmin Kim; Joon‐Kyu Lee (FEBS Open Bio)
To overcome genotoxicity, cells have evolved powerful and effective mechanisms to detect and respond to DNA lesions. RecQ Like Helicase‐4 (RECQL4) plays a vital role in DNA damage responses. RECQL4 is recruited to DNA double‐strand break (DSB) sites in a poly(ADP‐ribosyl)ation (PARylation)‐dependent manner, but the mechanism and significance of this process remain unclear. Here, we showed that the domain of RECQL4 recruited to DSBs in a PARylation‐dependent manner directly interacts with poly(ADP‐ribose) (PAR) and contains a PAR‐binding motif (PBM). By replacing this PBM with a PBM of hnRNPA2 or its mutated form, we demonstrated that the PBM in RECQL4 is required for PARylation‐dependent recruitment and the roles of RECQL4 in the DSB response. These results suggest that the direct interaction of RECQL4 with PAR is critical for proper cellular response to DSBs and provide insights to understand PARylation‐dependent control of the DSB response and cancer therapeutics using PARylation inhibitors.